PARTNERSHIP IN THE HOTEL INDUSTRY WITH VIRTUAL HOTEL OPERATOR (VHO) - zeehanfuad attamimi; Ika Ariani Kartini (International Journal of Law and Legal Ethics, 2022)
The hotel business is experiencing the development of a modern cooperation system, namely Virtual Hotel Operator (VHO) which is a company that has a system that has its own application that provides virtual services or remote internet. This study aims to analyze the partnership business system agreement between the hospitality industry and VHO. The research method uses a juridical empirical approach, research that will explore data through field surveys, and uses secondary and primary data sources which are analyzed through qualitative methods. The results of the study explain that the partnership between the hospitality industry and VHO uses a standard form of agreement that makes the hotel not have a bargaining position but VHO is included in a different type of partnership cooperation with partnerships in other hotel industries. There are several disadvantages and advantages in this form of cooperation. The conclusion of this research is that VHO does not cooperate with the franchise concept which is usually done in the hotel industry, namely using and utilizing the values ​​contained in its Intellectual Property Rights, but by implementing a profit-sharing cooperation system. Recommendations The Government needs to support the hotel industry. There is a need for a special law regarding the regulation of cooperation between the hotel industry and VHO in order to ensure certainty and legal protection in carrying out such cooperation.